2013
DOI: 10.1002/hyp.10059
|View full text |Cite
|
Sign up to set email alerts
|

Sea‐level rise impact on fresh groundwater lenses in two‐layer small islands

Abstract: The fresh groundwater lenses (FGLs) of small islands can be highly vulnerable to climate change impacts, including sea-level rise (SLR). Many real cases of atoll or sandy islands involve two-layer hydrogeological conceptualizations. In this paper, the influential factors that affect FGLs in two-layer small islands subject to SLR are investigated. An analytical solution describing FGLs in circular islands, composed of two geological layers, is developed for the simplified case of steady-state and sharp-interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 40 publications
1
61
1
Order By: Relevance
“…The effect of SLR on atoll island groundwater resources is expected to be as severe as that of future rainfall (Ketabchi, Mahmoodzadeh, Ataie‐Ashtiani, Werner, & Simmons, ). As sea level rises, and depending on beach slope, which typically ranges from 0.5% to 2% (Tsyban et al, ), seawater will inundate beachfronts leading to beach shoreline recession, also termed “land‐surface inundation” in island studies (Mahmoodzadeh, Ketabchi, Ataie‐Ashtiani, & Simmons, ; Morgan & Werner, ), which can be significant even for a small rise of sea level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of SLR on atoll island groundwater resources is expected to be as severe as that of future rainfall (Ketabchi, Mahmoodzadeh, Ataie‐Ashtiani, Werner, & Simmons, ). As sea level rises, and depending on beach slope, which typically ranges from 0.5% to 2% (Tsyban et al, ), seawater will inundate beachfronts leading to beach shoreline recession, also termed “land‐surface inundation” in island studies (Mahmoodzadeh, Ketabchi, Ataie‐Ashtiani, & Simmons, ; Morgan & Werner, ), which can be significant even for a small rise of sea level.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have been conducted for small coral islands. These studies (Bailey, Khalil, & Chatikavanij, ; Chui & Terry, ; Comte, Join, Banton, & Nicolini, ; Ketabchi et al, ; Morgan & Werner, ; Terry & Chui, ) are summarized in Table . Studies for other oceanic islands (Holding & Allen, ; Mahmoodzadeh et al, ; Sulzbacher et al, ) also are included to provide a broader range of methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that non-intrusive polynomial chaos expansions provided a reliable and yet computationally efficient surrogate of the original numerical model. Conceptualizing some global and significant concerns such as the effects of climate change (e.g., Ketabchi et al, 2014;Mahmoodzadeh et al, 2014) is one of areas which demand further examinations to identify how these impacts change the coastal groundwater management. As these issues (e.g., climate change-induced sea-level rise and variations in recharge rates) are essentially uncertain, stochastic conceptualization is compelled to properly distinguish between the various impacts and different SWI underlying factors (Werner et al, 2013).…”
Section: Future Research Challengesmentioning
confidence: 99%
“…Comprehensive reviews on SWI simulation approaches are given by Bear et al (1999) and Werner et al (2013). The SWI status depends on several factors including scale, aquifer properties, groundwater inflow and outflow, upconing due to well pumping, the tidal oscillation of the sea level, and climate change features such as sea-level rise and variations in recharge rate (e.g., Ataie-Ashtiani et al, 1999, 2013bKetabchi et al, 2014;Mahmoodzadeh et al, 2014) and there are unreliability or uncertainty in many of these factors, that cause the SWI analysis more complex .…”
Section: Introductionmentioning
confidence: 99%